A Clinical Study on the Effect of Shatahwadi Ghrita in the Management of Optic Atrophy (AYUSHDHARA, 2024)
Background and Objectives: Optic atrophy is an end stage condition where the optic nerve degenerates and leads to symptoms like vision loss. Objective of the present study was to evaluate the effect of Shatahwadi ghrita in the management of optic atrophy. Methods: 32 patients filling the inclusion criteria of optic atrophy were randomly selected for the study. Source of the data - Patients were selected from OPD and IPD of Shalakyatantra, S.D.M. College of Ayurveda and Hospital, Hassan. Shatahwadi ghrita was administered as Aschyotana, Pratimarsha nasya and Ghrita pana. Clinical signs and symptoms were given suitable scores according to its severity and assessed based on pre and post data gathered through pre- designed research proforma. The results having ‘p’ value less than